Driving the Workhorse: Maine’s Reliance on the Nearshore Environment - Brewer, Angela (Maine Policy Review, 2023)
The changing character of Maine’s coastal ecosystems has accelerated in full view of the users most reliant on nearshore habitats and the species they support. Adaptation and diversification facilitate continued harvest of Maine’s iconic ocean bounty, which supports the coastal economy despite compounding stresses from upland development, warmer and more acidic waters, and invasive species. Use intensification in the nearshore environment calls for coordinated discussions to nurture and innovate within and across habitats to preserve their longevity and sustain the people that depend on them. Recent legislative support for eelgrass and salt marsh mapping, and estuarine and marine water quality and shellfish and finfish contaminants monitoring, combined with private grants offered for coastal acidification research and climate action, provide opportunities to unify knowledge gathering along the narrow swath of Maine’s nearshore environment. Efforts being made by the Maine Department of Environmental Protection and environmental advocates within and outside our borders are furthering development of checks and balances on estuarine and marine nitrogen loading, devising and implementing creative solutions to allow co-existence of recreational boating and eelgrass, and facilitating restoration of nearshore habitats that buffer our shorelines, support fisheries, and temper climate change effects. Maine’s nearshore environment is experiencing challenges that should be met with knowledge gained from successes in more southerly latitudes. The multi-tiered wealth of Maine’s partnerships must be leveraged to maintain and improve nearshore habitat resilience while simultaneously respecting the outstanding resources so many of us have grown to rely upon.
Keywords: nearshore environment; coastal economy; use intensification